Angle‐dependent reflectivity of twill‐weave carbon fibre reinforced polymer for millimetre waves. Issue 6 (1st March 2018) - Artner, G.; Zöchmann, E.; Pratschner, S.; Lerch, M.; Rupp, M.; Mecklenbräuker, C. F.
Abstract : Twill‐weave carbon fibre reinforced polymer is measured as a reflector material for electromagnetic waves at 60 GHz. The reflectivity at millimetre wavelength shows a predominant direction, which coincides with the diagonal pattern of the twill's top layer. In the remaining directions, the investigated 2/2 twill‐weave composite's reflectivity is almost isotropic.